1989
DOI: 10.1007/bf01665008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of variant and parental-cross-protective immunity to immunogenic variants of a murine fibrosarcoma using the local adoptive transfer assay

Abstract: The purpose of this study was to characterize the lymphocyte populations responsible for rejection of immunogenic (Imm+) tumor variants, and the cross-protective immunity engendered by Imm+ variants against the weakly immunogenic parental tumor. Immunogenic clones of the weakly immunogenic methylcholanthrene-induced fibrosarcoma MCA-F have been generated using 1-methyl-3-nitro-1-nitrosoguanidine, 5-aza-2'-deoxycytidine, or ultraviolet radiation (UV-B; 280-320 nm). These clones grow progressively in immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In several tumor models, anti-tumor CD4+ T cells have proven capable of mediating tumor rejection or conferring protective immunity, even in the absence of CD8+ Tcells [12,[22][23][24]. Although CD4+ Tcells are non-cytolytic to most tumors, it has been demonstrated that direct cytolytic effects are not essential for the anti-tumor activity of CD4+ [22] or even CD8+ T cells [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several tumor models, anti-tumor CD4+ T cells have proven capable of mediating tumor rejection or conferring protective immunity, even in the absence of CD8+ Tcells [12,[22][23][24]. Although CD4+ Tcells are non-cytolytic to most tumors, it has been demonstrated that direct cytolytic effects are not essential for the anti-tumor activity of CD4+ [22] or even CD8+ T cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that dendritic APC themselves may play a greater role in the processing and presentation of at least certain Ag in vivo than monocytes/macrophages [16]. In particular, LC are critical for both the afferent and efferent limbs of contact hypersensitivity and transplantation rejection [9,17,181 and may play an essential role in anti-tumor immunosurveillance [19-211. That MHC class-I1 bearing APC primarily stimulate CD4+ Tcells is of particular interest, since in several tumor models anti-tumor CD4+ T cells or non-CD8+ T cells have proven capable of mediating tumor rejection or conferring protective immunity [12,[22][23][24]. In these models, the successful culture of anti-tumor CD4+ T cells has relied on immunization of animals against a tumor or purified tumor protein and subsequent in v i m restimulation of sensitized Tcells with macrophages or spleen cells pulsed with a purified tumor protein [22,251.…”
Section: Introductionmentioning
confidence: 99%